A Review on Fish Sensory Systems and Amazon Water Types With Implications to Biodiversity - Borghezan, Elio de Almeida; Pires, Tiago Henrique da Silva; Ikeda, Takehide; Zuanon, Jansen; Kohshima, Shiro (Frontiers in Ecology and Evolution, 2021)
The Amazon has the highest richness of freshwater organisms in the world, which has led to a multitude of hypotheses on the mechanisms that generated this biodiversity. However, most of these hypotheses focus on the spatial distance of populations, a framework that fails to provide an explicit mechanism of speciation. Ecological conditions in Amazon freshwaters can be strikingly distinct, as it has been recognized since Alfred Russel Wallace’s categorization into black, white and blue (= clear) waters. Water types reflect differences in turbidity, dissolved organic matter, electrical conductivity, pH, amount of nutrients and lighting environment, characteristics that directly affect the sensory abilities of aquatic organisms. Since natural selection drives evolution of sensory systems to function optimally according to environmental conditions, the sensory systems of Amazon freshwater organisms are expected to vary according to their environment. When differences in sensory systems affect chances of interbreeding between populations, local adaptations may result in speciation. Here, we briefly present the limnologic characteristics of Amazonian water types and how they are expected to influence photo-, chemical-, mechano- and electro-reception of aquatic organisms, focusing on fish. We put forward that the effect of different water types on the adaptation of sensory systems is an important mechanism that contributed to the evolution of fish diversity. We point toward underexplored research perspectives on how divergent selection may act on sensory systems and thus contribute to the origin and maintenance of the biodiversity of Amazon aquatic environments.